Post-discharge impact and cost-consequence analysis of prehabilitation in high-risk patients undergoing major abdominal surgery: secondary results from a randomised controlled trial. (October 2019) - Barberan-Garcia, A.; Ubre, M.; Pascual-Argente, N.; Risco, R.; Faner, J.; Balust, J.; Lacy, A.M.; Puig-Junoy, J.; Roca, J.; Martinez-Palli, G.
Abstract: Background: Prehabilitation may reduce postoperative complications, but sustainability of its health benefits and impact on costs needs further evaluation. Our aim was to assess the midterm clinical impact and costs from a hospital perspective of an endurance-exercise-training-based prehabilitation programme in high-risk patients undergoing major digestive surgery. Methods: A cost-consequence analysis was performed using secondary data from a randomised, blinded clinical trial. The main outcomes assessed were (i) 30-day hospital readmissions, (ii) endurance time (ET) during an exercise testing, and (iii) physical activity by the Yale Physical Activity Survey (YPAS). Healthcare use for the cost analysis included costs of the prehabilitation programme, hospitalisation, and 30-day emergency room visits and hospital readmissions. Results: We included 125 patients in an intention-to-treat analysis. Prehabilitation showed a protective effect for 30-day hospital readmissions (relative risk: 6.4; 95% confidence interval [CI]: 1.4–30.0). Prehabilitation-induced enhancement of ET and YPAS remained statistically significant between groups at the end of the 3 and 6 month follow-up periods, respectively (ΔET 205 [151] s; P =0.048) (ΔYPAS 7 [2]; P =0.016). The mean cost of the programme was €389 per patient and did not increment the total costs of the surgical process (€812; CI: 95% –878 – 2642; P =0.365). Conclusions: Prehabilitation may result in health value generation. Moreover, it appears to be a protective intervention for 30-day hospital readmissions, and its effects on aerobic capacity and physical activity may show sustainability at midterm. Clinical trial registration: NCT02024776.